2010
DOI: 10.1111/j.1365-2125.2010.03620.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic interactions of echinacea and policosanol with warfarin in healthy subjects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Echinacea and policosanol are commonly used herbal medicines which may be ingested by patients receiving warfarin. Echinacea has been implicated in interacting with drug metabolizing enzymes and policosanol has been shown to decrease platelet aggregation. The potential interaction of echinacea and policosanol with warfarin has not previously been investigated. WHAT THIS STUDY ADDS • Concomitant treatments with echinacea increased the apparent clearance of S‐warfari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Additionally, based on the measured IC50 values as percent of single dose, echinacea was observed to be a slightly more potent inhibitor of TAM metabolism as compared to ginseng. Previously, it has been shown that echinacea has had only moderate or no effect on conventional drugs in clinical settings [26][27][28][29], while the effects of ginseng have been reported to be even less [26,29,30]. In general, echinacea and ginseng are considered low risk for drug-herb interaction which is consistent with our data.…”
Section: Metabolic Inhibition By Echinacea and Ginsengsupporting
confidence: 93%
“…Additionally, based on the measured IC50 values as percent of single dose, echinacea was observed to be a slightly more potent inhibitor of TAM metabolism as compared to ginseng. Previously, it has been shown that echinacea has had only moderate or no effect on conventional drugs in clinical settings [26][27][28][29], while the effects of ginseng have been reported to be even less [26,29,30]. In general, echinacea and ginseng are considered low risk for drug-herb interaction which is consistent with our data.…”
Section: Metabolic Inhibition By Echinacea and Ginsengsupporting
confidence: 93%
“…Evidence from one study for the combination of Echinacea and warfarin was inconclusive (grade: low) [97]. …”
Section: Resultsmentioning
confidence: 99%
“…Results of one study showed no clinically important but a statistically significant decrease (grade: insufficient) in S-warfarin AUC ∞, an increase in drug clearance and an apparent increase in volume of distribution (GMRs: 0.92 (90% CI 0.85, 0.99); 1.09 (90% CI 1.01, 1.18); and 1.09 (95% CI 1.03, 1.18), respectively) [97]. …”
Section: Resultsmentioning
confidence: 99%
“…The policosanol tolerability has also been tested in children [66]. Moreover, policosanols seem to have no interaction with warfarin [67].…”
Section: Policosanolsmentioning
confidence: 99%